A discrete method of sphere-pipe intersecting curve for robot welding by offline programming. (June 2019) - Liu, Yan; Tang, Qiu; Tian, Xincheng
Highlights: Simulations have shown that the proposed sphere-pipe model can cover most of the intersection structures (commonly used in actual welding). Through the geometric analysis of the above model, this paper gives the parameter equations of this kind curve in different coordinate systems. For different calculation requirements, we can choose the curve equations in different coordinate systems to achieve the purpose of simplifying calculation. By studying the characteristics of intersecting curve, this paper gives the calculation method of maximum curvature, which determines the maximum arc length for curve discretization. This method simplifies the relevant formula and greatly reduces the amount of calculation. Based on the restraint of chord error in engineering, the discrete algorithm of intersecting curve by equal arc length is proposed. This algorithm ensures the accuracy of robot intersecting curve welding to the greatest extent. This paper takes the Puma560 industrial robot for simulation, and the simulation results are used to verify the feasibility and effectiveness of our method. Abstract: The sphere-pipe intersecting curve is a kind of spatial complex curve, which is controlled by robot in the sphere-pipe welding. In this paper, a discrete method for robot welding by offline programming is put forward. To move the robot with the specified curve trajectory, it need to be discretized to generate the robot motion instructions. As the core innovation of this paper, a discrete method of sphere-pipe intersecting curve is given according to the chord error limit and principle of equal arc length, which guarantees the accuracy of robot welding. To achieve this goal, this paper has done the following related works. First, the geometrical model of the sphere-pipe intersection is established, which can cover most of the intersection modes. Second, this paper gives the parameter equations in two different coordinate systems because the expression is very complex. This operation will simplify the subsequent calculations. Although the curve expression is simplified, it is very complicated to find the maximum based on the definition of curvature. After experimental analysis, this paper presents a simple and effective algorithm for the calculation of maximum curvature. Finally, this paper takes the Puma560 robot for simulation, and the simulation results are used to verify the feasibility and effectiveness of our method.